Digital libraries and educational practice: a case for new models - Sumner, Tamara; Marlino, Mary (Proceedings of the 4th ACM/IEEE-CS Joint Conference on Digital Libraries, 2004)
Educational digital libraries can benefit from theoretical and methodological approaches that enable lessons learned from design and evaluation projects performed in one particular setting to be applied to other settings within the library network. Three promising advances in design theory are reviewed - reference tasks, design experiments, and design genres. Each approach advocates the creation of 'intermediate' constructs as vehicles for knowledge building and knowledge sharing across design and research projects. One purpose of an intermediate construct is to formulate finer-grained models that describe and explain the relationship between key design features and the cognitive and social dimensions of the context of use. Three models are proposed and used as thought experiments to analyze the utility of these approaches to educational digital library design and evaluation: digital libraries as cognitive tools, component repositories, and knowledge networks.